HEMATOLOGICAL ASSESSMENT IN FOUR BRAZILIAN TELEOST FISH WITH PARASITIC INFECTIONS, COLLECTED IN FEEFISHING FROM FRANCA, São Paulo, BRAZIL - Tavares-Dias, Marcos; Moraes, Flávio Ruas de [UNESP]; Martins, Mauricio L. (Inst Pesca, 2008)
The effects of parasitic infections in condition factor, hematocrit, hemoglobin, mean corpuscular hemoglobin concentration (MCHC), and leucocytes and thrombocytes distribution in Piaractus mesopotamicus, Leporinus macrocephalus, hybrid tambacu (P. mesopotamicus x Colossoma macropomum and Brycon amazonicus collected in feefishing from Franca, São Paulo, Brazil were evaluated. Parasitized tambacu and L. macrocephalus had higher (p<0.05) condition factor than unparasitized fish. However, the contrary occurred in P. mesopotamicus and B. amazonicus. Changes in the hematocrit, hemoglobin and MCHC were not related to parasitism. Parasitic infections did not cause effect on leucocytes and thrombocytes percentage (p>0.05) of tambacu. In P. mesopotamicus parasitized by Monogenea Anacanthorus penilabiatus and dinoflagellate Piscinoodinium pillulare, increase in monocytes and decrease in thrombocytes percentage (p<0.05) were found. However, the same parasitic association in L. macrocephalus caused a decrease in lymphocytes percentage accompanied by increase in neutrophils percentage (p<0.05). In B. amazonicus, infection by Ichthyophthirius multifiliis, P. pillulare and monogeneans caused increase in neutrophils percentage.
Keywords: blood; condition factor; freshwater fish; leucocytes; hematology; parasites